Volume 1: 37th Computers and Information in Engineering Conference 2017
DOI: 10.1115/detc2017-67878
|View full text |Cite
|
Sign up to set email alerts
|

Design Review Using Virtual Reality Enabled CAD

Abstract: Computer Aided Design (CAD) has been crucial to the engineering design process since the 1960s due to the ability to create 2D and 3D design representations and easily incorporate design changes without the cost of physical prototypes. However, CAD is hindered by its hardware displaying 3D objects as 2D representations, causing a loss of realism compared to a physical prototype. This paper seeks to observe if increasing the realism of interaction between subjects and virtual prototypes using virtual reality ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
3
18
1
Order By: Relevance
“…Therefore, it is not clear whether the improved identification of folding steps in DI (see Figure 4) is because of the CAD features or because of the higher experience of using this technology. Nevertheless, the findings of increased understanding in DI do not relate to previous results as de Casenave and Lugo (2017) did not find significant differences in terms of design understanding between VR and DI. Furthermore, the findings of correctly identified folding steps do not relate to consistently better spatial perception in VR (Horvat et al, 2019;Paes et al, 2017;Satter and Butler, 2015).…”
Section: Difference Between Vr and DIcontrasting
confidence: 86%
See 1 more Smart Citation
“…Therefore, it is not clear whether the improved identification of folding steps in DI (see Figure 4) is because of the CAD features or because of the higher experience of using this technology. Nevertheless, the findings of increased understanding in DI do not relate to previous results as de Casenave and Lugo (2017) did not find significant differences in terms of design understanding between VR and DI. Furthermore, the findings of correctly identified folding steps do not relate to consistently better spatial perception in VR (Horvat et al, 2019;Paes et al, 2017;Satter and Butler, 2015).…”
Section: Difference Between Vr and DIcontrasting
confidence: 86%
“…the Mental Rotation Test (MRT) (Peters et al, 1995)). However, previous research failed to identify its effect on the level of design understanding (de Casenave and Lugo, 2017). Previous studies showed that VR has great potential to support the design review process.…”
Section: Design Reviewers' Expertisementioning
confidence: 99%
“…Previous research studies have often measured the spatial ability of participants employing different surveys or tests prior to the experimental tasks. For example, de Casenave and Lugo [11] used the Spatial Cognition Survey, while Calderon-Hernandez et al [48] employed the Purdue Spatial Visualization Test: Visualisation of Rotations. Participants' spatial ability was measured as an intrinsic-dynamic spatial skill of mental rotation in the conducted experiment.…”
Section: A Experimental Variables and Their Measuresmentioning
confidence: 99%
“…Design understanding and needed level of underlying spatial abilities depend on information input provided by a visual representation of a design solution [6]. During product development, designers use various representations, such as 2D engineering drawings, 3D CAD models and mock-ups or physical prototypes to visually present a design solution [11], [12]. These visual representations can be mediated by various technologies, such as conventional 2D user interface (a monitor display, a keyboard, and a mouse) or 3D user interfaces (an immersive virtual reality; IVR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation